Website Layout Design of Kurnia Advertising as a Promotion Media in the City of Malang - Indahsari, Rina Dewi; Rizqi, Afif Naufal (VCD: Journal of Visual Communication Design, 2021)
Layout is the basic framework that must be built in a design work. In this Kurnia Advertising promotional website, the power of layout in displaying information is dominated by white which gives the impression of a clean and simple design. Other elements use dominant colors of yellow, black and orange which are intended to give a cheerful and elegant feel. Product photos and detailed product information are presented on the website to provide more complete information to users. The ease of accessing the website and complete information are the strengths of this website to attract consumers to be interested in buying services from Kurnia Advertising. Tests carried out by distributing google forms to measure the effectiveness of website design and content were carried out on 50 respondents. The test results show that the website is quite effective in providing information to users with a simple design. In addition, the development of a website that is used as a promotional medium aims to make it easier for users to get information through features and the addition of a complex but structured menu so that the information conveyed can be more optimal. Keywords: website, layout, promotion media, user interface